2019
DOI: 10.3390/jcm8122079
|View full text |Cite
|
Sign up to set email alerts
|

Case-matched Comparison of Cardiovascular Outcome in Loeys-Dietz Syndrome versus Marfan Syndrome

Abstract: Background: Pathogenic variants in TGFBR1, TGFBR2 and SMAD3 genes cause Loeys-Dietz syndrome, and pathogenic variants in FBN1 cause Marfan syndrome. Despite their similar phenotypes, both syndromes may have different cardiovascular outcomes. Methods: Three expert centers performed a case-matched comparison of cardiovascular outcomes. The Loeys-Dietz group comprised 43 men and 40 women with a mean age of 34 ± 18 years. Twenty-six individuals had pathogenic variants in TGFBR1, 40 in TGFBR2, and 17 in SMAD3. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…Amongst individual case reports, the most frequently reported physical characteristics include: aortic aneurysms, abnormal uvula, arterial tortuosity, pectus deformity and arachnodactyly (Table 2). In cohort studies of patients with LDS type 1 (1,2,(12)(13)(14)(15), ranging from 12 to 176 individuals (Supplementary Table 3), the most frequently reported characteristics include: joint laxity (68%), arachnodactyly (62%), pectus deformity (51%), aneurysms of vessels other than the aorta (50%), arterial tortuosity (50%) and retrognathia (50%; Table 3). The presence of aortic aneurysms varied significantly between studies ranging from 17 to 100% and aortic dissections ranged from 17 to 25%.…”
Section: Lds Typementioning
confidence: 99%
See 1 more Smart Citation
“…Amongst individual case reports, the most frequently reported physical characteristics include: aortic aneurysms, abnormal uvula, arterial tortuosity, pectus deformity and arachnodactyly (Table 2). In cohort studies of patients with LDS type 1 (1,2,(12)(13)(14)(15), ranging from 12 to 176 individuals (Supplementary Table 3), the most frequently reported characteristics include: joint laxity (68%), arachnodactyly (62%), pectus deformity (51%), aneurysms of vessels other than the aorta (50%), arterial tortuosity (50%) and retrognathia (50%; Table 3). The presence of aortic aneurysms varied significantly between studies ranging from 17 to 100% and aortic dissections ranged from 17 to 25%.…”
Section: Lds Typementioning
confidence: 99%
“…The most frequently reported physical characteristics include: aortic aneurysms, hypertelorism, abnormal uvula, joint laxity, pectus deformity, scoliosis, arterial tortuosity, arachnodactyly (Table 2). In cohort studies of patients with LDS type 2 (1,2,12,(14)(15)(16), ranging from 12 to 265 patients (Supplementary Table 4), the most frequently reported features include: velvety skin (82%), malar hypoplasia (75%), easy bruising (67%), aneurysms of vessels other than the aorta (59%), arterial tortuosity (49%), high arched palate (48%) and pectus deformity (47%; Table 3). The prevalence of aortic aneurysm ranged from 23 to 75% as did a history of aortic dissection 16-35%.…”
Section: Lds Typementioning
confidence: 99%
“…High-throughput NGS data were generated on an Illumina sequencing platform. ROI sequences were aligned to the human reference genome (hg19) and visualized and evaluated by using the Sequence Pilot module SeqNext (JSI Medical Systems) [14,15].…”
Section: Genetic Analysismentioning
confidence: 99%
“…Typical cardiovascular features in LDS are dilatation of the aortic root at the level of the sinus of Valsalva, aneurysms affecting thoracic and abdominal aorta and arterial branches, as well as arterial tortuosity 1 , 5 . Cardiovascular manifestations tend to be more severe in LDS than in MFS 6 , however, a multi-center study has recently demonstrated a comparable cardiovascular outcome in individuals with MFS and LDS 7 . Heterozygous pathogenic variants in six genes cause LDS type 1–6: TGFBR1 , TGFBR2 , SMAD3 , TGFB2 , TGFB3 , and SMAD2 8 13 .…”
Section: Introductionmentioning
confidence: 96%